2008
DOI: 10.2528/pierl08040705
|View full text |Cite
|
Sign up to set email alerts
|

Fractal-Like Square Lattice of Air Holes

Abstract: Fractal structures have been widely used in many fields of science, such as biology, physics and chemistry. In this article, we analyze the basic properties of a fractal-like square lattice of air holes, with most of the holes having a lattice constant of Λ while others are repeated with a lattice constant of 2Λ. We change the radii of these holes and analyze their effects on the bandgap regions and transmission properties. The analysis conducted here is based upon band diagrams and 2D Finite difference time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Such a requirement becomes even more challenging when also a high degree of miniaturization is required. It has been demonstrated that fractal shapes [1]- [4] are suitable solutions for both miniaturization [5]- [10] and multi-band issues [11]- [14]. These results are enabled by two important properties of fractal geometries: the space-filling capability and the self-similarity.…”
Section: Introductionmentioning
confidence: 88%
“…Such a requirement becomes even more challenging when also a high degree of miniaturization is required. It has been demonstrated that fractal shapes [1]- [4] are suitable solutions for both miniaturization [5]- [10] and multi-band issues [11]- [14]. These results are enabled by two important properties of fractal geometries: the space-filling capability and the self-similarity.…”
Section: Introductionmentioning
confidence: 88%
“…A straight-forward application of the full-wave method [8][9][10][11][12][13] requires tremendous computer resources in order to sufficiently discretize 3-D (vectorial) field along an FBG fiber. It is possible, for example, to modify the recently published coupled transverse-mode integralequation (CTMIE) method [11][12][13] to accurately model the complex reflection and transmission coefficient matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on shielding effectiveness of metallic cavities with apertures were discussed [17][18][19][20]. The papers [21,22] described the fractional square and rectangular cavity resonator. In [23], modeling and analysis of the package and different mitigation techniques were used to make stable, resonance free microwave amplifier for a C-band space borne SAR payload.…”
Section: Introductionmentioning
confidence: 99%